A randomized controlled trial of larval therapy for the debridement of leg ulcers: Results of a multicenter, randomized, controlled, open, observer blind, parallel group study. Issue 1 (2nd December 2013) - Mudge, Elizabeth; Price, Patricia; Neal, Walkley; Harding, Keith G.
Abstract It has been known for centuries that the application of larvae is useful to heal certain wounds by facilitating debridement of necrotic tissue, 1 yet the efficacy of larval therapy continues to be debatable. This study compared the clinical effectiveness of a larval therapy dressing (BioFOAM) with a standard debridement technique (Purilon gel; hydrogel) in terms of time to debridement of venous (VLU) or mixed arterial/venous (MLU) leg ulcers. Data analyses were conducted on 88 subjects. Sixty‐four subjects completed the full study. Of these, 31 of the 32 (96.9%) patients who completed treatment in the larvae arm debrided fully, compared with 11 of the 32 (34.4%) patients who completed the hydrogel arm. In addition, 42 (48%) ulcers fully debrided within the 21‐day intervention phase, 31 (67.4%) from the larvae arm (n = 46), and 11 (26.2%) from the hydrogel arm (n = 42), which was statistically significant (p = 0.001) in support of larvae. A statistically significant difference was also observed between treatment arms with regard to numbers of dressing changes during the intervention phase of the study (p < 0.001) in that subjects in the larvae arm required significantly fewer dressing changes(mean = 2.83) than those in the hydrogel arm (mean = 5.40). There were no statistically significant differences in the clinical condition of the wound bed and surrounding skin by intervention. Subjects in the larvae arm experienced more ulcer‐related pain or discomfort than subjects in the hydrogel arm (p < 0.001). This study provided good evidence to show that larval therapy, in the form of a BioFOAM dressing, debrided VLU and MLU considerably more quickly than a hydrogel, although the possibility of resloughing should be closely monitored.